2013
DOI: 10.1371/journal.pntd.0002183
|View full text |Cite
|
Sign up to set email alerts
|

Phage Therapy Is Effective against Infection by Mycobacterium ulcerans in a Murine Footpad Model

Abstract: BackgroundBuruli Ulcer (BU) is a neglected, necrotizing skin disease caused by Mycobacterium ulcerans. Currently, there is no vaccine against M. ulcerans infection. Although the World Health Organization recommends a combination of rifampicin and streptomycin for the treatment of BU, clinical management of advanced stages is still based on the surgical resection of infected skin. The use of bacteriophages for the control of bacterial infections has been considered as an alternative or to be used in association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
81
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 55 publications
0
81
0
3
Order By: Relevance
“…The HK97 fold has been detected in every tailed phage capsid that has been imaged at sufficient resolution, including P22 11; 12; 13 , T4 14 , λ 15 , ϕ29 16 , T5 17; 18 , P2/P4 19 , epsilon15 20 , T7 21; 22 , the tailed-phage-like archaevirus HSTV-1 23 , in the base layer of the Herpesvirus (HSV1) major capsid protein 24 and in the bacterial comparments known as encapsulins 25 . With renewed interest in phage therapy to combat multiple-drug-resistant bacterial pathogens 26; 27; 28 , and an emerging interest in using bacteriophage capsids as platforms for nanotechnology 29 (http://www.nano.gov/) directed to the treatment of disease 30; 31 and the creation of new technologies 32; 33; 34; 35 , it is important to have a deep understanding of capsid structures and assembly pathways in order that they can be manipulated and utilized to the greatest extent.…”
Section: Introductionmentioning
confidence: 99%
“…The HK97 fold has been detected in every tailed phage capsid that has been imaged at sufficient resolution, including P22 11; 12; 13 , T4 14 , λ 15 , ϕ29 16 , T5 17; 18 , P2/P4 19 , epsilon15 20 , T7 21; 22 , the tailed-phage-like archaevirus HSTV-1 23 , in the base layer of the Herpesvirus (HSV1) major capsid protein 24 and in the bacterial comparments known as encapsulins 25 . With renewed interest in phage therapy to combat multiple-drug-resistant bacterial pathogens 26; 27; 28 , and an emerging interest in using bacteriophage capsids as platforms for nanotechnology 29 (http://www.nano.gov/) directed to the treatment of disease 30; 31 and the creation of new technologies 32; 33; 34; 35 , it is important to have a deep understanding of capsid structures and assembly pathways in order that they can be manipulated and utilized to the greatest extent.…”
Section: Introductionmentioning
confidence: 99%
“…The major reason behind this is that the bacteria can transit into a dormant state and remain as a latent infection within the body. This latent form of the bacteria is not acted upon by most drugs, making it difficult to eradicate the disease (20)(21)(22). Phages for mycobacteria were reported more than 7 decades ago (23,24).…”
mentioning
confidence: 99%
“…Methods to kill M. tuberculosis using mycobacteriophages already have been explored using the lytic mycobacteriophage TM4, which was introduced into a macrophage cell line harboring M. tuberculosis using M. smegmatis as a carrier, resulting in the reduction of pathogen counts (57,58). Phage D29, the model system used in this study, has been found to be effective against Mycobacterium ulcerans in a murine footpad model (22). It is possible that some of the ameliorative effects of phage treatment observed in these studies are due to the enhanced release of superoxides, which, as mentioned above, can act in trans not only on the bacteria producing them but also on the bystanders.…”
mentioning
confidence: 99%
“…The treatment with D29 mimotope also stimulated the increase in infi ltrating lymphocytes and macrophages. The study has demonstrated a potential of phage-based therapy against M. ulcerans infection, paving the way for the development of novel phage-based therapeutic approaches (45) . Phage-displayed peptides employed as vaccine candidates have two important advantages.…”
Section: Bacteriophages As Tools For the Development Of New Vaccinesmentioning
confidence: 97%